Glucose-mediated proliferation of a gut commensal bacterium promotes Plasmodium infection by increasing mosquito midgut pH - Wang, Mengfei; An, Yanpeng; Gao, Li; Dong, Shengzhang; Zhou, Xiaofeng; Feng, Yuebiao; Wang, Penghua; Dimopoulos, George; Tang, Huiru; Wang, Jingwen (Cell reports (Cambridge), 2021)
Plant-nectar-derived sugar is the major energy source for mosquitoes, but its influence on vector competence for malaria parasites remains unclear. Here, we show that Plasmodium berghei infection of Anopheles stephensi results in global metabolome changes, with the most significant impact on glucose metabolism. Feeding on glucose or trehalose (the main hemolymph sugars) renders the mosquito more susceptible to Plasmodium infection by alkalizing the mosquito midgut. The glucose/trehalose diets promote proliferation of a commensal bacterium, Asaia bogorensis, that remodels glucose metabolism in a way that increases midgut pH, thereby promoting Plasmodium gametogenesis. We also demonstrate that the sugar composition from different natural plant nectars influences A. bogorensis growth, resulting in a greater permissiveness to Plasmodium. Altogether, our results demonstrate that dietary glucose is an important determinant of mosquito vector competency for Plasmodium, further highlighting a key role for mosquito-microbiota interactions in regulating the development of the malaria parasite. [Display omitted] •Glucose/trehalose supplementation promotes Plasmodium infection in mosquitoes•Glucose/trehalose supplementation promotes the expansion of a gut commensal Asaia•Asaia remodels glucose metabolism and increases midgut pH•The pH increase induces Plasmodium gametogenesis and facilitates parasite infection Wang et al. show that glucose/trehalose supplementation promotes the expansion of a commensal bacterium Asaia that modulates glucose metabolism, resulting in an increase of mosquito midgut pH. The pH increase promotes Plasmodium berghei sexual development.